Conducting rapid qualitative interview research during the COVID-19 pandemic—Reflections on methodological choices - Wanat, Marta; Borek, Aleksandra J.; Pilbeam, Caitlin; Anthierens, Sibyl; Tonkin-Crine, Sarah (Frontiers in Sociology, 2022)
As the COVID-19 pandemic has shown, setting up studies in time to gather relevant, real-world data enables researchers to capture current views and experiences, focus on practicalities on the ground, and deliver actionable results. Delivering high quality rapid studies in healthcare poses several challenges even in non-emergency situations. There is an expanding literature discussing benefits and challenges of conducting rapid research, yet there are relatively few examples related to methodological dilemmas and decisions that researchers may face when conducting rapid studies. In rapidly-changing emergency contexts, some of these challenges may be more easily overcome, while others may be unique to the emergency, magnified, or emerge in different ways. In this manuscript, we discuss our reflections and lessons learnt across the research process when conducting rapid qualitative interview studies in the context of a healthcare emergency, focusing on methodological issues. By this we mean the challenging considerations and pragmatic choices we made, and their downstream impacts, that shaped our studies. We draw on our extensive combined experience of delivering several projects during the COVID-19 pandemic in both single and multi-country settings, where we implemented rapid studies, or rapidly adapted an existing study. In the context of these studies, we discuss two main considerations, with a particular focus on the complexities, multiple facets, and trade-offs involved in: i) team-based approaches to qualitative studies; and ii) timely and rapid data collection, analysis and dissemination. We contribute a transparent discussion of these issues, describing them, what helped us to deal with them, and which issues have been difficult to overcome. We situate our discussion of arising issues in relation to existing literature, to offer broader recommendations while also identifying gaps in current understandings of how to deal with these methodological challenges. We thus identify key considerations, lessons, and possibilities for researchers implementing rapid studies in healthcare emergencies and beyond. We aim to promote transparency in reporting, assist other researchers in making informed choices, and consequently contribute to the development of the rapid qualitative research.